2021
DOI: 10.3390/nu13124560
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Workplace-Based Diet and Lifestyle Interventions on Risk Factors in Workers with Metabolic Syndrome: A Systematic Review, Meta-Analysis and Meta-Regression

Abstract: Workplace health interventions are essential to improve the health and well-being of workers and promote healthy lifestyle behaviours. We carried out a systematic review, meta-analysis and meta-regression of articles measuring the association between workplace dietary interventions and MetS risk. We recovered potentially eligible studies by searching MEDLINE, the Cochrane Library, Embase, Scopus and Web of Science, using the terms “Metabolic syndrome” and “Occupational Health”. A total of 311 references were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…These analyses implicate that weight loss is a stronger influence for physiological features of MetS but has lesser impact on mental and work-related features when compared to changes in exercise capacity. This suggests that dietary induced weight loss is of stronger impact when addressing cardiovascular risk factors such as waist circumference, blood lipids, or blood glucose concentration, which was reported before [ 17 , 38 ]. In this regard, the Mediterranean Diet, in particular, showed beneficial effects on disease-related interventions with a focus on nutrition, with cardiovascular disease and MetS being the most investigated diseases for Mediterranean Diet [ 39 ].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…These analyses implicate that weight loss is a stronger influence for physiological features of MetS but has lesser impact on mental and work-related features when compared to changes in exercise capacity. This suggests that dietary induced weight loss is of stronger impact when addressing cardiovascular risk factors such as waist circumference, blood lipids, or blood glucose concentration, which was reported before [ 17 , 38 ]. In this regard, the Mediterranean Diet, in particular, showed beneficial effects on disease-related interventions with a focus on nutrition, with cardiovascular disease and MetS being the most investigated diseases for Mediterranean Diet [ 39 ].…”
Section: Discussionmentioning
confidence: 52%
“…In general, both activity and dietary changes should be addressed in patients with MetS, as data suggest that particularly the combination of diet and physical activity reduces disease risk factors [ 17 ]. Exercise in addition to dietary-induced weight loss is also crucial to preserve muscle mass as metabolically important tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the assessment performed through the CONSORT criteria, the evaluation of the level of evidence and recommendation of the studies included in this review was to a certain extent lower than that observed in current systematic reviews on occupational health [ 30 , 31 ]. The study of the non-significant time trend in document adequacy contradicted the expected evolution of increased fulfilment in the course of time.…”
Section: Discussionmentioning
confidence: 99%